Long donor leukocyte telomeres raise risk of severe COVID-19 in recipients of allogeneic hematopoietic cell transplant - Mendez, Kyra J. W.; Lai, Tsung-Po; Spellman, Stephen R.; Verhulst, Simon; Anderson, James; Saber, Wael; Gadalla, Shahinaz M.; Aviv, Abraham (Frontiers in Immunology, 2025)
IntroductionShort leukocyte telomeres are associated with an increased risk of severe COVID-19 in the general population, likely due to a weakened T-cell response to SARS-CoV-2. This may lead to an amplified neutrophil response, causing pulmonary damage. Allogeneic hematopoietic cell transplant (HCT) offers an experimental setting to examine further the role of telomere length (TL) in COVID-19 severity, as leukocyte TL in recipients post-HCT reflects TL in donor leukocytes before HCT and SARS-CoV-2 infection.MethodsWe examined the relationship between donor leukocyte TL pre-HCT and COVID-19 severity post-HCT in 87 HCT recipients hospitalized for COVID-19 between March 2020 and January 2022. Using the Telomere Shortest Length Assay (TeSLA), we measured leukocyte TL and the percentage of telomeres shorter than 3 kilobases.ResultsThe risk of severe COVID-19 in HCT recipients was associated with long telomeres (P=0.005) and a lower percentage of telomeres shorter than 3 kilobases (P=0.01) in donor leukocytes. Moreover, long donor leukocyte telomeres were associated with an increased risk of recipient mortality within four months after COVID-19 hospitalization (P=0.03).ConclusionsThese findings suggest that long donor leukocyte telomeres may trigger an excessive neutrophil response and severe COVID-19 in allogeneic HCT recipients, potentially due to a transplant-related but TL-independent weak T-cell response.